(untitled) (Research, Society and Development, 2022)
Objectives: To investigate the quality of sleep of students and the practice of physical exercise by students of the Physiotherapy course at the State University of Goiás during the COVID-19 pandemic. Methodology: A cross-sectional and descriptive study was carried out. The survey was carried out using a questionnaire sent via a Google Forms link, in which sociodemographic questions and the Brazilian version of the Pittsburgh Sleep Quality Index (PSQI-BR) were collected through a single session to assess sleep quality. The sample consisted of 103 students of the Physiotherapy course at the State University of Goiás (UEG). Project approved by UEG’s CEP (Opinion 5,045,803). Descriptive statistics (means, standard deviation, relative and absolute frequencies) using the JAMOVI software, version 2.2.5. Results: The evaluation of the sleep quality of Physical Therapy students - investigated through the PSQI-BR - showed that 65% had poor sleep quality and 24.3% identified with the presence of sleep disorders. The practice of physical exercise was also analyzed and 79% believe that the contagion scenario had an influence on their physical exercise habits. Discussion: Given the pandemic scenario, most of the sample had poor sleep quality, sleep disorders and changes in physical exercise. Conclusion: The quality of sleep was analyzed and there were dysfunctional sleep patterns with poor sleep quality and the practice of physical exercises was also influenced by the pandemic in Physical Therapy students at UEG.